PENGARUH PEMBERIAN PROBIOTIK Lactobacillus acidophilus DAN Bifidobacte-rium sp TERHADAP PERFORMA PRODUKSI AYAM PETELUR YANG DIINFEKSI Escherichia coli - Khoirul Huda; Widya Paramita Lokapirnasari; Soeharsono Soeharsono (Universitas PGRI Semarang, 2019)
The purpose of this study is to determine the use of probiotics Lactobacillus acidophilus and Bifidobacterium sp on feed consumption and Hen Day Production (HDP) laying hens which infected by Escherichia coli. Arround 120 layers at the age of 25 weeks are divided into six treatments. Each treatment consisted of factor a (infection and non-infection Escherichia coli) and factor b (basal feed, AGP and probiotics). The result of this study shows that giving probiotic has taken an effect (p<0,05) on the feed consumption and HDP. The infection factor takes effect (p <0.05) on HDP but it does not take effect (p>0,05) on the feed consumption. There is interaction among probiotic factor and infection (p>0.05) on HDP but it has no effect (p> 0.05) on feed consumption. The highest feed consumption is found in the giving of non-infectious probiotics that is 114.7 g and the highest HDP which is from the giving of non-infectious probiotics is 98.6 %. In conclusion, the giving of probiotic Lactobacillus acidophilus and Bifidobacterium sp are able to produce well perform product and the high profit.